Level of awareness of personnel in hospital services related to the donation process: A Spanish and Latin American multicenter study - Ríos Zambudio, Antonio; López-Navas, Ana; Ayala-García, Marcos; Sebastián, María José; Abdo-Cuza, Anselmo; Alán, Jeannina; Martínez-Alarcón, Laura; Ramírez, Ector Jaime; Muñoz, Gerardo; Palacios, Gerardo; Suárez-López, Juliette; Castellanos, Roberto; et al. (The Journal of heart and lung transplantation, 2012)
Services related to the donation and transplantation process are fundamental for developing solid organ transplantation and procuring organs from deceased donors. This study was conducted to analyze the attitude toward deceased organ donation among hospital personnel working in donation- and transplantation-related services in hospitals in Spain and Latin America. Nine hospital centers within the “International Donor Collaborative Project” were selected (Spain, Mexico, Cuba, and Costa Rica). A random employee sample was taken and stratified according to the type of service and job category in transplant-related hospital services. Of the 925 employees surveyed, 78% were in favor of donation. By job category, attitude was more favorable among physicians (89%; p < 0.001). By type of service, attitude was more positive among personnel in transplant patient follow-up units (87%; p = 0.018). By country, the Cubans were most in favor (91%), followed by the Mexicans (81%), the Costa Ricans (77%), and the Spanish (70%; p < 0.001). Other factors were age (p < 0.001), sex (p = 0.005), considering the possibility of needing a transplant (p = 0.002), understanding the concept of brain death (p < 0.001), being in favor of living donation (p < 0.001), having discussed the subject of donation and transplantation within the family and the partner (p < 0.001), carrying out pro-social activities (p = 0.002), and concern about mutilation after donation (p = 0.002). Transplant-related personnel had a favorable attitude toward deceased donation, although it was not as positive as we would expect, especially among non-physicians. This attitude needs to be improved because of the negative effect that can result in organ donation. There were pronounced differences between countries, and the discordance between attitude and actual deceased donation rates in each country is notable.